Space, Language and Power: The Rhetoric of Street Protests - Bekar Mira (My University, 2015)
This paper explores the rhetoric of street protest banners and slogans used as a means of performing dissatisfaction and the role of the street where a network of relationships is built among actors with unequal power and with shared beliefs about specific social situations. Drawing upon Berns’ (1995: 195) view that “for the 21st century people, English serves a wider range of purposes, well beyond face-to-face contact through mass communication and media, including print, audio-visual, and electronic media, than ever before in history”, and Bourdieu’s (1989) discussion on the symbolic struggles over the perception of the social worlds, this paper focuses on the relationship between the use of English, as a means for communicating dissatisfaction at a global level, and the street, used as a medium for performing joint social action. The language and visual rhetoric of protest slogans and banners written in English were analyzed using the principles of visual rhetoric for the purposes of this study. The local contexts included Iran, Serbia, Macedonia, and Ukraine. This exploratory study shows how local historical and political imagery and the sense of belonging to the world-wide social and political processes are negotiated.
Keywords: street protest, social space, visual rhetoric, lingua franca, power